Simple method for the quantitative analysis of thin copolymer films on substrates by infrared spectroscopy using direct calibration - Tazreiter, Martin (Anal Methods, 2017)
The chemical composition of a copolymer drives many important material properties and quantification in terms of comonomer volume fraction is thus of practical relevance for many studies. Infrared spectroscopy is one of the most common techniques for compositional analysis but it usually relies on manual evaluation of baselines and peak heights, which can be rather inaccurate and become a laborious task when having multiple spectra to evaluate. On the contrary, Maxwell's theory of electrodynamics can be used to calculate the complex index of refraction from measured spectra promising a more accurate quantification. Since this procedure is rather involved, we propose a simple in-house developed IR-quantification routine to automatically evaluate the comonomer volume fractions of thin copolymer films by using the Bouguer–Lambert–Beer approximation after correcting the baseline of all absorbance spectra automatically. This method was experimentally evaluated on over 40 thin polymeric coatings synthesized by initiated chemical vapor deposition on silicon substrates. The samples comprised a wide range of different compositions and were synthesized from four different monomers, with single films consisting of up to three components. All data obtained by our routine was compared with data from spectroscopic ellipsometry and with X-ray photoelectron spectroscopy data of selected samples. The comparisons show that the IR-quantification routine reliably evaluated the polymer composition even when the involved comonomers exhibited similar chemistry, as it is the case for methacrylic acid cross-linked with ethylene glycol dimethacrylate.